Developing Kaggle Notebooks Pave your way to becoming a Kaggle Notebooks Grandmaster - Preda, Gabriel; Preda, Gabriel; Sculley, D.; Goldbloom, Anthony (Packt Publishing, 2023)
Printed in Color Develop an array of effective strategies and blueprints to approach any new data analysis on the Kaggle platform and create Notebooks with substance, style and impact Leverage the power of Generative AI with Kaggle Models Purchase of the print or Kindle book includes a free PDF eBookKey FeaturesMaster the basics of data ingestion, cleaning, exploration, and prepare to build baseline modelsWork robustly with any type, modality, and size of data, be it tabular, text, image, video, or soundImprove the style and readability of your Notebooks, making them more impactful and compellingBook DescriptionDeveloping Kaggle Notebooks introduces you to data analysis, with a focus on using Kaggle Notebooks to simultaneously achieve mastery in this fi eld and rise to the top of the Kaggle Notebooks tier. The book is structured as a sevenstep data analysis journey, exploring the features available in Kaggle Notebooks alongside various data analysis techniques. For each topic, we provide one or more notebooks, developing reusable analysis components through Kaggle's Utility Scripts feature, introduced progressively, initially as part of a notebook, and later extracted for use across future notebooks to enhance code reusability on Kaggle. It aims to make the notebooks' code more structured, easy to maintain, and readable. Although the focus of this book is on data analytics, some examples will guide you in preparing a complete machine learning pipeline using Kaggle Notebooks. Starting from initial data ingestion and data quality assessment, you'll move on to preliminary data analysis, advanced data exploration, feature qualifi cation to build a model baseline, and feature engineering. You'll also delve into hyperparameter tuning to iteratively refi ne your model and prepare for submission in Kaggle competitions. Additionally, the book touches on developing notebooks that leverage the power of generative AI using Kaggle Models.What you will learnApproach a dataset or competition to perform data analysis via a notebookLearn data ingestion and address issues arising with the ingested dataStructure your code using reusable componentsAnalyze in depth both small and large datasets of various typesDistinguish yourself from the crowd with the content of your analysisEnhance your notebook style with a color scheme and other visual effectsCaptivate your audience with data and compelling storytelling techniquesWho this book is forThis book is suitable for a wide audience with a keen interest in data science and machine learning, looking to use Kaggle Notebooks to improve their skills and rise in the Kaggle Notebooks ranks. This book caters to: Beginners on Kaggle from any background Seasoned contributors who want to build various skills like ingestion, preparation, exploration, and visualization Expert contributors who want to learn from the Grandmasters to rise into the upper Kaggle rankings Professionals who already use Kaggle for learning and competing